Determinants of Net Asset Value of Islamic Mutual Funds in Indonesia - Ficky Septiana; M. Nur Rianto Al Arif (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
Net asset value is one of the indicators used in measuring the performance of a mutual fund. This study aims to examine what factors determine the net asset value of Islamic mutual funds in Indonesia. By using the vector error correction model, this study found that in the short term all variables did not affect the net asset value. But the composite stock price index and the rate of return have a long-term effect. These results indicate that the company must strengthen the company's internal aspects to improve the performance of the Islamic mutual funds it manages.